The dynamics of the South Pacific split jet in austral winter - Patterson, M (2020)
The wintertime atmospheric circulation in the southern hemisphere is characterised by a zonally asymmetric, spiral-like pattern. This includes a strong jet over the Indian Ocean region, which bifurcates downstream into subtropical and polar front branches, known collectively as the South Pacific split jet. The location of the split jet, over Australia and New Zealand, means that this system exerts a considerable influence on the climate of these countries, while the jets also affect the climate of East Antarctica and southern South America.